1959
DOI: 10.1111/j.1365-2621.1959.tb17307.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Histology and Texture of Elberta Peaches From Trees of High and Low Levels of Nitrogen Nutrition

Abstract: Commercial canning of freestone peaches, such as Elbertas, often results in tissue sloughing and a ragged appearance by comparison with the firmly coherent texture of canned clingstone varieties. In some areas, however, plantings of freestone varieties predominate and have increased to the point that quality improvement in their use in the canned fruit market has received serious consideration. This is the situation in the state of Washington (10) where it has been found that the canning quality of Elberta pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1959
1959
2013
2013

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The histological origins, development and maturation of the different tissues of the green bean pod serve to explain the wide range within which specialized tissue structure and composition may variously influence textural problems encountered in processing. Similar interrelationships between special tissue conditions and texture have been encountered in other processed fruits and vegetables (Powers et al, 1958;Reeve, 1964aReeve, ,b, 1947Reeve, , 1953Reeve, , 1959Reeve, , 1965Reeve et al, 1959Reeve et al, , 1966Sterling, 1955;and Ster-ling et al, 1961) . Textural problems encountered in green beans have centered in three major areas: (1) sloughing of the skins in cooked, canned and frozen products ; (2) stringiness and/or toughness due to over-maturity of fibrous tissues ; and (3) loss of crispness due to the influence of over-blanching and different freezing treatments.…”
Section: Discussionsupporting
confidence: 57%
“…The histological origins, development and maturation of the different tissues of the green bean pod serve to explain the wide range within which specialized tissue structure and composition may variously influence textural problems encountered in processing. Similar interrelationships between special tissue conditions and texture have been encountered in other processed fruits and vegetables (Powers et al, 1958;Reeve, 1964aReeve, ,b, 1947Reeve, , 1953Reeve, , 1959Reeve, , 1965Reeve et al, 1959Reeve et al, , 1966Sterling, 1955;and Ster-ling et al, 1961) . Textural problems encountered in green beans have centered in three major areas: (1) sloughing of the skins in cooked, canned and frozen products ; (2) stringiness and/or toughness due to over-maturity of fibrous tissues ; and (3) loss of crispness due to the influence of over-blanching and different freezing treatments.…”
Section: Discussionsupporting
confidence: 57%
“…An example of the influence of cell size upon textural appearance has been described for Elberta peaches grown under high (or excessive), and low N nutritional conditions (Reeve and Neufeld, 1959). Smaller cell size and high N nutrition were associated with a firm, finely textured appearance in contrast to the larger cells and soft, ragged textural quality of those grown under conditions of low N nutrition .…”
Section: B Peachesmentioning
confidence: 99%
“…Son (1959) related softening of peaches and pears to the thinning process in cell walls and to the ease of cell separation. Morphology of peaches was also studied by Sterling (1962), Reeve (1959) and Reeve and Neufeld (1959), and that of pears by Sterling (1954). Reeve and Leinbach (1953) and Reeve (1953) investigated histology of apple tissue and reported that the composition of middle lamella materials, rather than the gross chemical analysis, affects textural quality.…”
Section: A Texture and Structurementioning
confidence: 99%